Optimal step-size LMS equalizer algorithm - Solmaz, Cercis Ozgur; Oruc, Ozgur; Kayran, Ahmet Hamdi (IEEE, 2011)
In this paper, an optimal step-size finding algorithm for LMS is presented. The algorithm runs iteratively and convergence to the equalizer coefficients by finding the optimal step-size which minimizes the steady-state error rate at each iteration. No initialization for the step-size value is required. Efficiency of the proposed algorithm is shown by making a performance comparison between some of the other LMS based algorithms and optimal step-size LMS algorithm.